Biographical suspension and liminality of Self in accounts of severe sciatica. (December 2018) - Saunders, Benjamin; Bartlam, Bernadette; Artus, Majid; Konstantinou, Kika
Abstract: Sciatica is a common form of low back pain (LBP) that has been identified as distinct both in terms of the persistence and severity of symptoms. Little research has explored individual experiences of sciatica, and none focuses on individuals with the most severe, long-lasting symptoms who may experience the most profound impact. This paper addresses this gap through proposing a theoretical framework for understanding such experiences, that of biographical suspension as a form of liminality of Self. Twenty semi-structured interviews were conducted with individuals with severe sciatic symptoms between January 2016‒March 2017, as part of the UK-based SCOPiC (SCiatica Outcomes in Primary Care) randomised controlled trial. Data were analysed thematically using the constant comparison method. The concept of 'biographical suspension', originally developed in LBP, emerged as one whereby individuals put life on-hold in the expectation of an eventual return to their former, pain-free selves. Deeper analysis extended this concept to a form of liminality, whereby individuals are caught between pre- and post-sickness selves, unable to fully identify with either. This liminality is underpinned by ongoing beliefs about sciatica as a temporary and fixable 'injury' rather than long-term 'illness', even among those with long-lasting symptoms. This led to a disjuncture between individuals' ongoing pain beliefs and experiences, resulting in longer-term psychological impacts. Biographical suspension is further conceptualised as an experiential stage giving rise to four distinct short-term trajectories: i) symptom resolution leading individuals to occupy a clearly post-liminal state; ii) remaining in suspended liminality; iii) ongoing symptoms leading to a post-liminal state of resignation; ix) a state of being both between sickness and wellness, and straddling hope and fear; thus exemplifying differing states of liminality experienced over time. Findings have implications for the support provided in clinical settings to individuals who may struggle to self-manage due to sustained liminality of Self. Highlights: First paper to explore lived experiences of individuals with most severe sciatica. Individuals experience biographical suspension, conceptualised as liminality. Liminality is underpinned by conceptualisation of sciatica as a fixable 'injury'. Biographical suspension can give rise to four distinct experiential trajectories. Differing forms of liminality identified throughout course of pain trajectory.